The media handbook : a complete guide to advertising media selection, planning, research, and buying - Katz, Helen E. (New York: Routledge, 2022)
"The eighth edition of The Media Handbook continues to provide a practical introduction to the media planning and buying processes. Starting with the broader context in which media planning occurs, including a basic understanding of competitive spending and target audiences, the book takes readers through the fundamentals of each media channel, leading to the creation of a media plan. Throughout, concepts and calculations are clearly explained. This new edition reflects the changes in how people consume media today: a new chapter on how audiences are defined and created reorganization of the media channel chapters to cover planning and buying together expanded coverage of digital formats in all channels added discussion of measurement completely updated data and examples. The Media Handbook, Eighth Edition is the ideal text for courses in media planning and buying in advertising/communication departments. The Companion Website to the book includes resources for both students and instructors. For students, there is a list of key media associations and new sample media planning exercise scenarios with accompanying practice spreadsheets. Instructors can find lecture slides and sample test questions to assist in their course preparation. Please visit www.routledge.com/cw/katz"--
Revised edition of the author's The media handbook, 2019.
Includes bibliographical references and index.
Keywords: Advertising media planning; Mass media and business; Marketing channels